STATUS SOSIAL EKONOMI ORANG TUA DAN HUBUNGANNYA DENGAN PRESTASI BELAJAR SISWA - Zulvia Trinova; Ayu Lestari Hasibuan; Nini Nini (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2021)
The socioeconomic status of the students' parents varies widely. The socioeconomic status of a good family can have an effect on the growth and physical development of children, as well as the growth of intelligence, talents, interests, health, readiness, and maturity. The quantitative method used is based on the positivism philosophy of the population and samples were selected in the completion of this study. Samples were taken randomly, using research instruments to collect data. Data were analyzed quantitatively to test the hypothesis. The sample amounted to 70 people in this study. The results showed that the socioeconomic status of parents was in the high criteria with a frequency of 24 (34.28%). At low criteria with a frequency of 46 (65.71%). The findings about learning achievement were that 26 (37.14%) students were in the high category, 44 (62.85%) students were in the low category. In conclusion, there is a significant positive correlation between the socioeconomic status of parents and the learning achievement of students in class VIII SMPN 11 Padang.